Comparison of serum Vascular Cell Adhesion Molecule (VCAM) level among epithelial ovarian cancer patients and healthy women - Rizwana Hussain; Saba Khaliq (Journal of the Pakistan Medical Association, 2024)
Objective: To compare serum vascular cell adhesion molecule levels among ovarian cancer patients of different standardised grades, and in relation to healthy controls. Method: The case-control study was conducted from 6.2.2018 to 1.8.2021 after approval form the ethics review board of the University of Health Sciences, Lahore, Pakistan, and comprised females aged 20-70 years diagnosed with ovarian cancer and tentatively planned for surgical procedures in group A, and healthy controls in group B. From all the subjects, 2.5ml blood was taken in a green-top tube. The tubes were centrifuged, and the serum was separated within an hour of sample collection. The Eppendorf tubes were labelled and stored at -20°C. The samples were thawed, and, following the manual protocol, they were subjected to vascular cell adhesion molecule enzyme-linked immunosorbent assay. Cancer antigen 125 values before surgery and 6-8 months post-surgery were recorded from available laboratory reports. Also, group A was categorised in line with the International Federation of Gynaecology and Obstetrics stage classification. Data was analysed using SPSS 24. Results: Of the 80 female subjects, 40(50%) were group A cases and 40(50%) were group B controls. The overall mean age was 48±12 years. Overall, 55(68.7%) women were aged <55 years and 25(31.3%) were aged >55 years. Within group A, 20(50%) had cancer stage I-II and 20(50%) had stage III-IV. Overall median vascular cell adhesion molecule was 72.40ug/L (interquartile range: 1857.40ug/L), with 71.15ug/L (interquartile range: 616.60ug/L) in group A and 74.10ug/L (interquartile range: 1848.70ug/L) in group B. Significant correlation was found between cancer stage and vascular cell adhesion molecule level (rho=0.73; p=0.003). Conclusion: There was a decreased level of vascular cell adhesion molecule level in epithelial ovarian cancer cases compared to healthy controls. A positive association was observed between ovarian cancer stage and vascular cell adhesion molecule level. Key Words: VCAM, FIGO, Correlation, Serum marker, Ovarian cancer.